(3GdYhO hGdedGgi hGSeGFgGs - (3GdeanqVd Hf SdeI Hf YGUe, CHh WGdH,J (B290 (3g` s ((3jGbhJ GdeSJYUei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jgH Gdage def jTGA , hCYhP HGddg ef GOYGA eGdG MSf abOjekG eG gJc Pdc ef jJYQV dg s
(3BNQgG (B:s
(3CeG GdgRL agh GdNaja GdPi jeTi Ydjg hjdgi hjSJNa GdMdbhe hcGf GdZfGA Cgd Gdjef HOYi GdMHbi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B314s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe YGQa YGeg (B- (3U (B65 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI eUhQg Yf CMeO GdKGdK HGSJGfhd (B((3afhf LejdI (B533) s
Keywords: (3GdehSjbi hGdZfGAs